2001
DOI: 10.1016/s0008-6363(01)00223-1
|View full text |Cite
|
Sign up to set email alerts
|

Transmural repolarisation in the left ventricle in humans during normoxia and ischaemia

Abstract: Transmural repolarisation differences within the ventricular wall of the human heart were absent at cycle lengths within the physiological range but also during prolonged cycles. During early (global) ischaemia repolarisation changed equally in subepicardial and subendocardial regions and transmural homogeneity of repolarisation was preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
88
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(100 citation statements)
references
References 36 publications
11
88
1
Order By: Relevance
“…The results of our simulation suggest that the physiological morphologies of T waves are generated mainly by the transmural distribution of APD, although the contribution of the apicobasal gradient is also important. Although recent studies suggest that the cancellation effect in the intact heart can minimize transmural dispersion (5,41,42), a large apicobasal gradient is required to observe positive T waves in limb and left precordial leads under such conditions (Fig. 4C).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results of our simulation suggest that the physiological morphologies of T waves are generated mainly by the transmural distribution of APD, although the contribution of the apicobasal gradient is also important. Although recent studies suggest that the cancellation effect in the intact heart can minimize transmural dispersion (5,41,42), a large apicobasal gradient is required to observe positive T waves in limb and left precordial leads under such conditions (Fig. 4C).…”
Section: Discussionmentioning
confidence: 97%
“…During surgery or in animal experiments, subjects receive anesthetic agents that may block sodium and/or delayed rectifier potassium currents, causing preferential shortening of the APD of M cells (31). Furthermore, the plunge electrode technique used in many studies may not necessarily probe the whole area and depth of the ventricular wall (42,48). In a recent study, optical mapping revealed the distribution of APD in human ventricular tissue (12); however, only the posterior wall wedge was examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant transmural repolarization gradients dictated the characteristics of the voltage signal recorded across the isolated ventricular wall, analogous to the ECG T wave. In contrast, a number of studies (15,42,19) in human hearts have suggested that under physiological conditions, electrotonic influences abolish transmural electrical gradients during repolarization. These data question the importance of transmural gradients of repolarization in the ECG T wave, the origin of which remains controversial after decades of investigation (30,32).…”
mentioning
confidence: 94%
“…3, panel IV, as well as in previous studies (Yan et al, 1998b;Gima and Rudy, 2002;Idriss and Wolf, 2004;Ritsema van Eck et al, 2005). It should be noted however, that, while there is a large body of evidence supporting the existence of transmural heterogeneities in ionic currents and electrophysiological properties of ventricular tissue, some experimental studies have documented little or no transmural differences in APD in vivo (Anyukhovsky et al, 1996(Anyukhovsky et al, ,1999Taggart et al, 2001;Conrath et al;.…”
Section: Transmural Electrophysiological Heterogeneities In the Ventrmentioning
confidence: 56%